Pengaruh Program Pengembangan Profesional Berkelanjutan (PKB) Terhadap Kompetensi Profesional dan Pedagogis Guru PAI SD Negeri di Kabupaten Selebar Kota Bengkulu - Reki Oetalu; Suhirman Suhirman; Mindani Mindani (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
The objectives of this study are (1) to analyze the magnitude of the influence of the Continuous Professional Development Program (PKB) on the competence of elementary school teachers in Bengkulu City. (2) to analyze the magnitude of the influence of the Continuous Professional Development Program (PKB) on the Pedagogy of Elementary School Teachers in Bengkulu City. The type of research used in this study is quantitative research, the research instrument used is a questionnaire, the data analysis technique used is descriptive statistics, basic assumption tests, classical assumption tests, and hypothesis testing using simple linear regression, t-test. Research Results: (1) There is an influence of the Continuous Professional Development Program (PKB) on the Professional Competence of Elementary School Teachers in Bengkulu City as shown in the calculated t (2.053) > t table (5% = 1.70) and the significance level is 0.046 < 0.05. So this test shows that Ha is accepted. This means that there is an influence of the Continuous Professional Development Program (PKB) on the Professional Competence of Bengkulu City. (2) There is an influence of the Continuous Professional Development Program (PKB) on the pedagogy of PAI teachers in Public Elementary Schools in Bengkulu City as shown in the calculated t (2.862) > t table (5% = 1.70) and a significance level of 0.007 < 0.05. So this test shows that Ha is accepted. This means that there is an influence of the continuous professional development program (PKB) on the pedagogy of PAI teachers in Public Elementary Schools in Bengkulu City.